Representasi Maskulinitas dan Ketangguhan dalam Iklan OPPO A5 Pro Denny Sumargo: Semiotika Roland Barthes - Aleina Faradebi; Gibbran Prathisara (MUKASI: Jurnal Ilmu Komunikasi, 2026)
This study aims to analyze the representation of masculinity in the advertisement "OPPO A5 Pro | Mainstay Partner in Every Challenge" which features Denny Sumargo as a construction of male identity in technology-based media. Advertising is understood as a meaning-forming agent that reproduces gender ideology through a system of visual signs. This study used a descriptive qualitative approach with the method of non-participant observation of seven advertising Scenes as an analysis unit. The framework of analysis is based on Roland Barthes' semiotics which includes levels of denotation, connotation, and myth, and is supported by traditional and contemporary concepts of masculinity to reinforce the interpretive process. Secondary data were obtained from the scientific literature relevant to the study of semiotics and masculinity. The results of the study show that masculinity is represented through the visualization of physical toughness, the ability to face challenges, emotional stability, protective roles, and the integration of technology as part of masculine performance. These representations form a hybrid masculinity that combines traditional masculine values with modern technological competence. These findings confirm that the OPPO A5 Pro advertisement utilizes masculinity as a visual communication strategy to strengthen product image while contributing to the communication study regarding the formation of masculinity myths in contemporary digital media.